Hardships in Mountain Livelihood: Findings from Yari Village, Humla District (Geographical Journal of Nepal, 2011)
This paper aims at analyzing livelihoods of people of rural mountain areas highlighting the case of Yari village located in the north-western part of Humla district in Mid-western development region, Nepal. The study has been based on primary data collected through group discussions and key informant’s interview during May 2007. As in other mountainous areas of Nepal, people of Yari village perform a number of different activities for their livelihoods. Agriculture, forest product collection, homemade production activities, hotel/catering and wage laboring are the main livelihood options and survival strategies adapted by local people. However, people’s livelihood in this area is hard and insecure due to various adversities. The shortage of facilities and services, adverse climate, food deficiency, remoteness, lack of awareness, poor access to market and water stress are the main adversities faced by local people.The Geographical Journal of Nepal, Vol. 8-9, 2010-2011: 83-91